AN ELECTROCHEMICAL METHOD FOR STUDYING HIGH OXYGEN ACTIVITY EFFECTS IN TEXTURED YBA2CU3O7-X BULK AND THICK-FILM SAMPLES - Huang, H; Grovenor, C (1993)
The oxygen stoichiometry of melt textured YBa2Cu3O7-χ bulk samples and textured thick film samples has been controlled and improved by an electrochemical method. The thermodynamic properties of melt textured YBa2Cu3O7-χ bulk samples at very high oxygen activities were studied by this electrochemical method. The reaction products were analysed by XRD diffraction, EPMA and explained by thermodynamic calculation. Three possible 5 phase equilibria were identified in the system. The results show the electrochemical method is an effective way to generate a high oxygen activity environment at the surface of YBa2Cu3O7-χ. © 1993.